2012
DOI: 10.1088/0004-637x/752/2/121
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Collapse and Dynamo Waves in Global Direct Numerical Simulations

Abstract: Magnetic fields of low-mass stars and planets are thought to originate from self-excited dynamo action in their convective interiors. Observations reveal a variety of field topologies ranging from large-scale, axial dipole to more structured magnetic fields. In this article, we investigate more than 70 three-dimensional, self-consistent dynamo models obtained by direct numerical simulations. The control parameters, the aspect ratio and the mechanical boundary conditions have been varied to build up this sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
165
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(187 citation statements)
references
References 49 publications
19
165
3
Order By: Relevance
“…Charbonneau 2010). Although modern solar-type dynamo models reproduce the "regular" part of the behaviour of the large-scale solar magnetic field (Ghizaru et al 2010;Brown et al 2011;Schrinner et al 2012;Gastine et al 2012;Käpylä et al 2012), it is still challenging to extend the integration time over several magnetic cycles as needed to reproduce a Maunder-like minimum (see, however, Passos & Charbonneau 2014;Augustson et al 2015). Thus, while the MM is identified as a special mode of the solar dynamo, we are not yet able to precisely model it.…”
Section: Consequences Of the Maunder Minimummentioning
confidence: 96%
“…Charbonneau 2010). Although modern solar-type dynamo models reproduce the "regular" part of the behaviour of the large-scale solar magnetic field (Ghizaru et al 2010;Brown et al 2011;Schrinner et al 2012;Gastine et al 2012;Käpylä et al 2012), it is still challenging to extend the integration time over several magnetic cycles as needed to reproduce a Maunder-like minimum (see, however, Passos & Charbonneau 2014;Augustson et al 2015). Thus, while the MM is identified as a special mode of the solar dynamo, we are not yet able to precisely model it.…”
Section: Consequences Of the Maunder Minimummentioning
confidence: 96%
“…Direct numerical simulations showed that models with low Rossby numbers (i.e., fast rotating stars) generate strong dipolar magnetic fields (Schrinner et al 2012). These fields amplify Lorentz forces able to suppress Coriolis forces, and hence can effectively suppress DR (Gastine et al 2012).…”
Section: Comparison To Theorymentioning
confidence: 99%
“…As the depth of the convection zone decreases, the dipolarity breaks down rendering the rotation nonuniform (Schrinner et al 2012). This effect could explain the strong increase of ΔΩ around T eff > 6000 K. Browning (2011) provided an explanation for the shallow increase of α towards cooler stars.…”
Section: Comparison To Theorymentioning
confidence: 99%
“…high mass and very low mass stars) interested readers may refer to (e.g. Browning et al 2004;Brun et al 2005;Dobler et al 2006;Brown et al 2008;Christensen et al 2009;Featherstone et al 2009;Augustson et al 2011;Cai et al 2011;Morin et al 2011;Schrinner et al 2012, and references therein). Convection plays a key role in transporting the star's heat by having strong correlations between vertical motions and temperature fluctuations.…”
Section: Convection and Large Scale Flowsmentioning
confidence: 99%
“…The key results can be summarized as follow: 3-D numerical simulations of dynamo action in solar-like stars have revealed a large range of behavior, from steady dynamo, to irregular and cyclic ones Racine et al 2011;Gastine et al 2012;Schrinner et al 2012;Augustson et al 2013;Nelson et al 2013;Schrinner et al 2014, and references therein).…”
Section: Nonlinear Dynamo Effect Magnetic Activity and Cyclesmentioning
confidence: 99%